The Impact of Cooperative Learning and Contextual Teaching on Problem-Solving Skills and Student Responsibility in High School Mathematics - Hutabarat, Dina Safira; Harahap, Tua Halomoan; Nasution, Marah Doly (Journal of English Language and Education, 2025)
Education in Indonesia faces significant challenges in aligning with global advancements, particularly in enhancing students' problem-solving skills and fostering a sense of responsibility. This study aims to investigate the impact of Cooperative Learning and Contextual Teaching and Learning (CTL) models on improving these two critical aspects of high school mathematics education. Using a quasi-experimental design, the study involved two classes at SMA Negeri 1 Rantau Utara, Labuhanbatu Regency, Indonesia. Class X-D was assigned as the experimental group, implementing Cooperative Learning, while Class X-E served as the control group, utilizing the CTL model. Data were collected through pre-tests and post-tests to measure problem-solving skills and questionnaires to assess student responsibility. The data were analyzed using ANOVA with SPSS 27 for Windows. The results revealed that both learning models significantly improved students' problem-solving skills and responsibility. However, the Cooperative Learning group demonstrated a higher level of improvement compared to the CTL group, suggesting that collaborative learning enhances mathematical understanding and responsibility more effectively. This study underscores the importance of transitioning from conventional teaching methods to innovative, student-centered approaches. The findings imply that optimizing the application of Cooperative Learning and CTL can significantly contribute to improving the quality of education in Indonesia.